German firms in service trade - Markus Kelle; Jörn Kleinert (Kiel University, Department of Economics, 2010)
We provide firm-level evidence concerning four key facts of services trade in Germany. First, not only firms classified as service firms, but also firms from all industries export and import services. Second, service trade patterns are fairly similar to those in goods trade. Most notably, service trade is dominated by a few large firms that serve many countries, sell several service products, and often export and import services. Differences in firms' trade values are result from differences in all three margins of trade. Third, there is a strong concentration of firms on one core market and service. Fourth, the patterns are surprisingly similar for services exports and imports.
Keywords: D21; F14; L80; 330; service trade; firm heterogeneity; intensive and extensive margins of trade; Internationaler Dienstleistungsverkehr; Dienstleistungssektor; Multinationales Unternehmen; Deutschland